A Main Group Gallium(III) Complex Derived from 2-Acetylpyrazine N4-phenylthiosemicarbazone: Synthesis, Crystal Structure and Biological Evaluation. Issue 5 (3rd May 2016) - Lu, Yanli; Ma, Pengtao; Li, Mingxue; Chen, Danyun; Zou, Xueyan
Abstract : Up to now, main group gallium(III) complexes with thiosemicarbazones have been comparatively rare. Here, a main group six-coordinated gallium(III) complex [Ga(L)2 ]NO3 ·H2 O (1 ) (HL = 2-acetylpyrazine N 4 -phenylthiosemicarbazone) has been synthesized and characterized by elemental analysis, IR and UV/Vis spectroscopy, mass spectrometry, and single-crystal X-ray diffraction. The cytotoxicity data suggest that 1 exhibits significant antiproliferative activity in vitro against three human cancer cells. Its possible apoptotic mechanism has been evaluated in HepG2 cells.1 induces a dose-dependent apoptosis in HepG2 cells and the apoptosis is associated with reduction of mitochondrial membrane potential.